PENERAPAN STRATEGI RELATING, EXPERIENCING, APPLYING, COOPERATING, DAN TRANSFERING (REACT) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA: REACT: Berpikir Kreatif: Matematika - Lamlam Patimah; Lia Saniah (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2020)
This research is motivated by the lack of critical thinking skills and the ability to think creatively mathematical mathematical students. This study reviews, Upgrades Critical Thinking Mathematical and Thinking Skills Creative Mathematical and differences between students who apply Learning Strategies Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) with students who received conventional learning models, and relationships critical thinking skills and mathematical creative thinking ability of students. The method used in this study is a mixed methods embedded type. The study population were students of class X SMK Pasundan I Cianjur enrolled in the academic year 2015/2016. The samples used were two classes of 14 existing classes. The instrument used to collect data in the form of instrument test critical thinking skills and the ability to think creatively mathematically, attitude scale, observation and interview sheet. Data were analyzed using mean difference test ie t-test (quantitative) and descriptions (qualitative). The results showed that Improvement of critical thinking skills of students who apply strategies Learning Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) better than students who use learning models conventional.